The effect of bend radius on the impulse transfer characteristics of V-hulls - Shekhar, Vinay Ramaswami (Department of Mechanical Engineering, 2016)
This work is based primarily on the effects of V-tip bend radii on the impulse transfer to V-plates subjected to localised blast loading. Three rigid V-plates with V-angles of 60°, 90° and 120° were designed and fabricated from steel plates. Blast tests with PE4 charges ranging from 19 g to 58 g at a stand-off distance (SOD) of 34mm were performed. The geometric scaling was based on the dimensions of the TM-57 landmine and the Casspir APC MK II. In the numerical model, the optimum element length for the air mesh was obtained by performing a mesh convergence study on the Arbitrary Lagrangian-Eulerian (ALE) mesh, and validated using the impulse values measured from a 58 g detonation onto a 120° V-plate as it resulted in the highest impulse. Element lengths of 1.5, 2.0 and 3.0mm were investigated. Element lengths of 1.5 and 2.0mm both produced accurate results, though the run-time for an element length of 2.0mm was significantly lower. A validation study compared the numerically predicted impulses with those of the experiments and the results were found to be within an acceptable percentage variation. Hence a 2.0mm element length was chosen for the Arbitrary Lagrangian-Eulerian mesh.